German Cartel Regulation Under the Decree of 1923 - Kessler, William C. (Quarterly Journal of Economics, 1936)
Journal Article German Cartel Regulation Under the Decree of 1923 Get access William C. Kessler William C. Kessler Colgate University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 50, Issue 4, August 1936, Pages 680–693, https://doi.org/10.2307/1891098 Published: 01 August 1936